African feminism/western feminism: contradictory or complementary (2010)
The term feminism is very complex to define as Chandra Mohanty admits in her introduction to Third World Women and the Politics of Feminism. This essay looks at the heated debate often generated by discourse on African and Western feminisms and concludes that even though there are differences between them as a result of their cultural and socio-contexts, they can still borrow a lot from each other.